2016
DOI: 10.1038/nchembio.2268
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal lipid sensors identify transbilayer asymmetry of plasma membrane cholesterol

Abstract: Controlled distribution of lipids across various cell membranes is crucial for cell homeostasis and regulation. We developed an imaging method that allows simultaneous in situ quantification of cholesterol in two leaflets of the plasma membrane (PM) using tunable orthogonal cholesterol sensors. Our imaging revealed marked transbilayer asymmetry of PM cholesterol (TAPMC) in various mammalian cells, with the concentration in the inner leaflet (IPM) being ~12-fold lower than that in the outer leaflet (OPM). The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

17
256
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 199 publications
(276 citation statements)
references
References 55 publications
(92 reference statements)
17
256
3
Order By: Relevance
“…It is likely that cholesterol concentration in the cellular membranes which D4 cannot bind to is lower than 30 mol % and/or environments around cholesterol like phospholipids composition inhibit binding of D4 to cholesterol in the membranes. To solve this issue, a couple of novel and excellent cholesterol probes derived from D4 have been developed by introducing a variety of mutations which decrease the threshold for cholesterol-binding to D4 [66,72]. …”
Section: Cholesterol Biosensors Derived From Perfringolysin O Thetmentioning
confidence: 99%
See 4 more Smart Citations
“…It is likely that cholesterol concentration in the cellular membranes which D4 cannot bind to is lower than 30 mol % and/or environments around cholesterol like phospholipids composition inhibit binding of D4 to cholesterol in the membranes. To solve this issue, a couple of novel and excellent cholesterol probes derived from D4 have been developed by introducing a variety of mutations which decrease the threshold for cholesterol-binding to D4 [66,72]. …”
Section: Cholesterol Biosensors Derived From Perfringolysin O Thetmentioning
confidence: 99%
“…To decrease still high threshold for cholesterol-binding to D4H (D4 D434S ), other point mutations were introduced in D4 in addition to D434 [72]. A recent study identified three amino acid residues (Y415, Q433, and A463) in D4, which determine the affinity of D4 to cholesterol [72].…”
Section: Cholesterol Biosensors Derived From Perfringolysin O Thetmentioning
confidence: 99%
See 3 more Smart Citations